Study of species richness of grasshopper (ordo orthoptera) in Beriri Jarak, Lombok Island, Indonesia - Moh. Liwa Ilhamdi; Muhammad Syazali; Mursidul Almiah (Jurnal Pijar Mipa, 2023)
The number of species of grasshoppers (Orthoptera) in Indonesia is very large, but the successfully identified species still need improvement. It then causes many of the existing species to be identified. This study aimed to determine the grasshopper species (Orthoptera) types in the Hamlet of Otak Kebon, Beriri Jarak Village. This exploratory, descriptive research uses a qualitative approach. Sampling was carried out in May 2022 in three habitat types: gardens, fields, and rice fields. Absolute and relative methods were carried out in sampling. The samples obtained were then identified using field guides and available literature to obtain existing species richness data. The results showed that there were 15 species, namely: Valanga nigricornis, Conozoa hyaline, Oedaleus infernalis, Chorthippus brunneus, Trimerotropis pallidipennis, Chorthippus albomarginatus, Ceracris kiangsu, Melanoplus bispinosus, L. migratoria manilensis Meyen, Trimerotropis occulens, Locusta migratoria, Austracris guttulosa, Atractomorpha crenulate, Leptophyes punctatissima, and Gryllus bimaculatus. The species found belong to two suborders, namely Caelifera and Ensifera. The species are divided into four families: Acrididae, Pyrgomorphidae, Tettigoniidae, and Gryllidae. The Acrididae family dominates the existing species. In addition, 13 species were also found that still needed to be recorded in previous studies, bringing the total to 43 species.